Investigation of anaerobic co- digestion process effects on the removal of COD and TKN from Mashhad's landfill leachate and cow dung - HOSEIN ALIDADI; Ali Asghar Najafpoor; somayeh etemadi mashhadi; Batoul Mohebrad; aliakbar dehghan (Mashhad University of Medical Sciences, 2018)
Introduction: Waste leachate contains hazardous organic compounds such as nitrogen compounds and high concentrations of poisonous compounds; the remediation of these pollutants from the environment is considered as a global problem. These pollutants make serious environmental problems through their penetration into groundwater and bioaccumulation. Therefore, leachate treatment is essential with suitable and appropriate methods. Anaerobic digestion is considered as one of the most cost-effective methods for this mean. This study aimed to evaluate the efficiency of an anaerobic digester in simultaneous removal of chemical oxygen demand (COD) and TKN from landfill leachate during the process of anaerobic co-digestion for landfill leachate and fresh cow dung. Materials and Methods: In this study, landfill leachate of Mashhad and cow dung was mixed in 3/1, 1/1 and 1/3 ratios. These treatments were exposed under anaerobic digestion with same conditions such as environmental temperature. COD and TKN were measured at the beginning and the end of the process. Results: In the control treatment, COD decreased about 5% and the reduction of TKN was 9.09%. Whilst COD reduction was about 65%, 75%, and 70% in the treatments of 3/1, 1/1 and 1/3 Ratio respectively. Also, TKN decreased 33.26, 82.16 and 84.73% in the 3/1, 1/1 and 1/3 Ratio correspondingly. Conclusion: The results of this study indicated that the applied method is an efficient and economical approach for elimination of COD and TKN from waste leachate. Because it not only is considered as an environmentally friendly method for this regard, but also it will also make economic benefits from methane production.